Faktor-Faktor yang Berhubungan dengan Status Gizi Ibu Hamil Pada Trimester III di Klinik Tsuraya Dabuk Rejo Kecamatan Lempuing Kabupaten OKI Tahun 2024 - Frantika Fitrianing Tyas; Intan Sari; Rini Gustina Sari; Minarti (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Nutritional status is an indicator of success in meeting nutritional needs during pregnancy. Pregnant women need nutrition in large quantities to meet the nutritional needs and growth of the fetus. The aim of the research is to determine the factors related to the nutritional status of pregnant women in the third trimester at the Tsuraya Dabuk Rejo Clinic, Lempuing District, OKI Regency in 2024. This research design uses an analytical survey with a cross sectional method. The population in this study were all third trimester pregnant women who had their pregnancy checked at the Tsuraya Dabuk Rejo Clinic, Lempuing District, OKI Regency from May to June 2024, totaling 53 pregnant women. The sampling technique uses total sampling where all members of the population are sampled. The sample in this study was 53 pregnant women. The analysis technique used Univariate, Bivariate (Chi square). Based on the results of the Chi Square statistical test, there is a relationship between knowledge and the partial nutritional status of pregnant women in the third trimester at the Tsuraya Dabuk Rejo Clinic, Lempuing District, OKI Regency in 2024, the Chi-Square result obtained is p value = 0.001, there is a relationship between education and nutritional status Partial nutrition of pregnant women in the third trimester at the Tsuraya Dabuk Rejo Clinic, Lempuing District, OKI Regency. In 2024, the Chi-Square results obtained p value = 0.001, there is a relationship between economic status and partial nutritional status of pregnant women in the third trimester at the Tsuraya Dabuk Rejo Clinic. Lempuing District, OKI Regency in 2024, the Chi-Square result obtained was p value = 0.001. It is hoped that the results of this research can be an illustration for the Tsuraya Dabuk Rejo Clinic to further improve health services, especially services for examining the nutritional status of pregnant women.